PSYCHOLINGUISTIC BASIS OF LISTENING COMPREHENSION - Shaxnoza Qo‘yliyeva Rustamovna (Scholar Express Journal, 2023)
The article examines the theoretical information on listening comprehension skills and explores the psycholinguistic foundations of listening comprehension skills. The effect of listening comprehension on the quality of education and the difficulties in this process, the experiences of practical teaching of listening and comprehension in various ways are covered as much as possible
Keywords: listening comprehension; speech activity; vocal speech